Pengaruh Posisi Biji dan Pupuk Organik Cair terhadap Pertumbuhan Bibit Kakao - Billy Yudha Syahputra; Razali Razali; Yunida Berliana; Ahmad Nadhira (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2021)
Introduction: This study was aimed to examine the effect of beans positions of the fruit and Liquid Organic Fertilizer (LOF) on the growth of the cocoa seedlings (Theobroma cacao ) in early nurseries. Materials and Methods: This study was conducted at the agricultural experiment land, Universitas Tjut Nyak Dhien, Medan Helvetia District, Medan City from April to June 2020. This study used a Randomized Block Design (RBD) within two factors. The first factor was beans position of the fruit (B0= peduncular, B1= median, B2= apical). The second factor was LOF application (D0= un-treated, D1= 3 ml.l-1, D2= 5 ml.l-1). The variables including radicle length, seedlings height, number of leaves, leaf area, stem diameter, and root fresh weight were then processed using ANOVA and BNT at the rate of 5%. Results: The beans position of the cocoa fruit was an insignificant effect on all parameters of seedlings. LOF application was significant on seedlings height at 4, 6, and 8 weeks after planting (WAP) and also the number of leaves at 8 WAP, but it had an insignificant effect on radicle length, leaf area, stem diameter, and root fresh weight. The interaction of beans position of the fruit and LOF application on the vegetative growth of cocoa seedlings in the early nursery also did insignificant in all parameters of this study.